Biomonitoring of air pollution by lichen diversity in the urban area of Setif, Algeria - AMINA BELGUIDOUM; RIMA HAICHOUR; TAKIA LOGRADA; MESSAOUD RAMDANI (Society for Indonesian Biodiversity, 2022)
Abstract. Belguidoum A, Haichour R, Lograda T, Ramdani M. 2021. Biomonitoring of air pollution by lichen diversity in the urban area of Setif, Algeria. Biodiversitas 23: 970-981. The use of living organisms in air quality monitoring has received increasing attention in recent years. Lichens, pioneer and colonizing organisms, are directly sensitive to environmental changes. This results in a loss of vitality or complete destruction of the thallus. The objective of this study is to assess and map the air quality of the Setif region, Algeria by lichens, using bio-indication indices. For air quality assessment, lichen species frequency, the Shannon-Wiener index, Atmospheric Purity Index (IAP), and Air Quality Index (IAQ) were used. Sixty stations were sampled across the region, representing the various level of landscape factors and anthropogenic activities. The study recorded 54 lichen species in urban areas of Setif belonged to 29 genera and 19 families, of which crustose and foliose, were the most common in the region. The pollution indicators (IAP, IAQ) showed an important correlation between them and a difference between rural and urban ecosystems. Anthropized urban areas showed very high air pollution. This is probably due to industrial and agricultural activities, but especially to gas emissions from vehicles. The majority of studied stations belonged to an area with very high atmospheric pollution. In addition, the presence of the species Xanthoria parietina in all the stations studied facilitates to use of it as a reliable biomonitor of plant tolerance to pollutants in urban ecosystems.